Diet high in α-linolenic acid up-regulate PPAR-α gene expression in the liver of goats - Ebrahimi, Mahdi; Rajion, Mohamed Ali; Goh, Yong Meng; Farjam, Abdoreza Soleimani; Oskoueian, Ehsan; Jafari, Saeid (Pontificia Universidad Católica de Valparaíso, 2015)
Background: There is little information on the effects of diets containing high α-linolenic acid (C18:3n-3) on liver lipid composition and lipogenic gene expressions. In this study fourteen goats (Capra aegagrus hircus) were fed either a flaxseed oil (FSO) supplemented diet containing high α-linolenic acid or a control diet without added flaxseed oil (CON) for 100-d to evaluate the effects on liver lipid composition and the gene expression of peroxisome proliferator-activated receptors (PPAR-α) and stearoyl-CoA-desaturase (SCD) in the liver. Results: An increase in the levels of C18:3n-3 and C20:5n-3, C22:5n-3, C22:6n-3 was observed in the liver of FSO-treated goats. There was a significant (P < 0.05) up-regulation of PPAR-α gene expression and downregulation of SCD gene in the liver of goats fed the high α-linolenic acid diet. Conclusions: In conclusion, genes associated with the control of fatty acid (FA) conversion (SCD and PPAR) were affected by the α-linolenic acid supplementation in the goat diet. It is suggested that PPAR-α is the key messenger responsible for the translation of nutritional stimuli into changes in hepatic gene expression.